Hubungan Usia dan Kadar Prostate Specific Antigen (PSA) dengan Derajat Histopatologi Adenokarsinoma Prostat di RSUD Abdoel Wahab Sjahranie Samarinda - Pratiwi, Novita Eka Tyas; Riastiti, Yudanti; Irawiraman, Hadi; Danial, Danial (Jurnal Kesehatan Andalas, 2023)
Adenocarcinoma prostate generally occurs in older adults and maybe because of increase in prostate-specific antigen (PSA) levels.  It is essential to know the relationship between age and PSA levels with histopathological grade to determine the appropriate management in cases of prostate adenocarcinoma. Objective: To determined  the relationship between age and  PSA levels with the histopathological grade of prostate adenocarcinoma patients at Abdoel Wahab Sjahranie General Hospital, Samarinda. Methods: The research design was analytic observational with a cross-sectional study approach. The data was taken from the medical records of prostate adenocarcinoma patients at Abdoel Wahab Sjahranie Hospital Samarinda from 2018 until 2022 using the total sampling method. 52 patients met the inclusion criteria. Bivariate analysis using the Chi-square test. Results:This study showed that there was no relationship between age (p=0.433) and PSA levels (p=0.347) with the histopathological grade of prostate adenocarcinoma patients at Abdoel Wahab Sjahranie General Hospital, Samarinda. Conclusion: There was no significant relationship between age and PSA levels with the histopathological grade of prostate adenocarcinoma at Abdoel Wahab Sjahranie Hospital, Samarinda.Keywords: adenocarcinoma prostate, age,  histopathological degree, PSA levels